(untitled) (Archives of Mechanics - Test, 2001)
As polycrystaline ice undergoes creep deformation over long time-periods, it develops a fabric (oriented structure) and associated, strain-induced anisotropy. In the paper, a frame-indifferent orthotropic constitutive model for secondary creep of ice is formulated, in which the strain-rate is expressed in terms of the deviatoric stress, strain, and three structure tensors based on the principal deformation axes. As an illustration, the model is used to determine the evolution of the creep response of ice to continued uniaxial compression and simple shearing.